Assessment of adverse drug reaction profile of the disease-modifying anti-rheumatic drugs at the department of orthopaedics in a tertiary care hospital, Silchar, Assam, India - Kairi, Vijoy S.; Chakravarty, Pinaki; Sipani, Arun Kumar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The mainstay of treatment of Rheumatoid Arthritis (RA) is the use of the disease-modifying anti-rheumatic drugs (DMARDs). Methotrexate, sulfasalazine and hydroxychloroquine are some of the DMARDs which are used in combination for the treatment of RA. The current study was undertaken to assess the adverse drug reactions (ADRs) of DMARDs that are commonly encountered with the treatment of RA. Methods: The present study was designed as a prospective, observational study on newly diagnosed patients with RA. Patients diagnosed with RA above 18 years (excluding pregnant women) of either sex who were prescribed DMARDs in combination were included. ADRs reported spontaneously by the patients and also responses obtained in a questionnaire related to likely ADRs from the patients was recorded in the case record form. Statistical analysis was done using graph pad and p value <0.05 was considered to be statistically significant. Results: A total of 47 patients attending the Outpatient Department of Orthopaedics, Silchar Medical College and Hospital, Silchar, Assam, India were screened for the study. ADRs were monitored up to the last visit on 41 patients excluding the patients who were lost and who were not able to adhere to the treatment. A total of 27 ADRs were reported from 19 ADR forms. Gastrointestinal manifestations were the most common adverse effects of combination DMARDs seen in 10 patients (24.39%). Severity assessment done using modified Hartwig and Siegel scale that showed majority of the ADRs were mild (74.07%). Conclusions: Present study showed that DMARDs are well-tolerated and have an acceptable toxicity profile as majority of ADRs seen were mild. It was however difficult to prevent the occurrence of ADRs. Proper monitoring of therapy is needed for early recognition of ADRs.